THE EFFECT OF BUTON MODIFIED BITUMEN MODULUS ON ASPHALT CONCRETE ÃâÃâ WEARING COURSE - TARUNA ZEGA (NIM: 26914309), RIZAK
The design methods of flexible pavement structures currently recognized two types of approaches: empirical methods and mechanistic methods. Mechanistic methods of pavement structural design have been developed over the past three decades. Since the 1970s, the characteristics of asphalt mixtures have begun to be understood in the presence of testing instruments that can directly measure the modulus value of a material such as the Direct Shear Rheometer (DSR) test kit and the Universal Material Testing Apparatus (UMATTA). The model used to calculate the bitumen stiffness modulus (Sbit) are the Van der Poel Nomogram and Ullidtz formula with certain limitations, whereas the mathematical model that can be used to calculate the stiffness modulus of asphalt mixture (Smix) is Bonnaure et.al (1977), Asphalt Institute method (1982) and Nottingham method (Brown, et al., 1984). This study attempts a new contribution to the sequence of asbuton research, where the study aims to validate the model used for unmodified bitumen and compare it with modified bitumen with asbuton. The bitumen stiffness modulus (Sbit) is in addition influenced by changes in temperature and loading time received by bitumen, also depending on the type of bitumen used and the type of modification performed both for the improvement of rheological properties and mechanistic properties of bitumen. The modification is of course expected to also contribute to improving the modulus value (Smix) of asphalt mixture using modified bitumen, which in this study the modification is by adding pure extraction of asbuton by 8% weight of bitumen. The Van der Poel model tends to be more suitable for use in determining the Sbit value by adjusting for its value in order to approximate the Sbit value of the DSR test. Asphalt Institute model is more recommended to be used in determining the value of Smix due to the resulting Smix value tend to be consistent to high temperature changes.